Efficient simulation of Hybrid Renewable Energy Systems - Migoni, Gustavo Andres (2016)
This article explores the usage of novel tools for realistic modeling and efficient simulation of Hybrid Renewable Energy Systems (HRES). Using the object oriented Modelica language, a new library providing component models such as photovoltaic (PV) cells, proton exchange membrane (PEM) fuel cells, electrolyzers, hydrogen storage tanks, batteries and electronic converters is developed and used to build different HRES models. Since the components are represented under realistic assumptions, the resulting models exhibit frequent discontinuities, strong non-linearities and combinations of slow and fast dynamics (i.e. stiffness). As these features impose severe limitations to classic numerical simulation solvers, we analyze the use of a new family of numerical algorithms called Quantized State Systems (QSS) that overcome most of those difficulties. The results obtained show that these algorithms applied to realistic HRES are more than one order of magnitude faster than the most efficient classic solvers, allowing to simulate these systems in reasonable times.